Peranan Dompet Dhuafa Waspada Dalam Pemberdayaan Masyarakat Miskin Melalui Pengembangan Usaha Mikro Kecil (UMK) di Kota Medan - Shafwan Ismail; Sri Sudiarti; M Ridwan (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2018)
This research was conducted in Dompet Dhuafa Waspada which has been managing productively zakat, the zakat received by Dompet Dhuafa Waspada is utilized first through programs that have been carried out then the results will be given to mustahiq zakat. This study examines the role of Dompet Dhuafa Waspada as the manager of zakat in the utilization of productive zakat. The research method used is qualitative, that is by describing data and facts that appear in the existing research, analyzed using descriptive, analytical and critical methods with SWOT analysis with aggressive strategies. Based on this research, it was found that. The collection of zakat, infaq and shadaqah funds is done by various means, such as auto zakat (Infaq Card), donation, teledonation, Donation via online banking, Donation via visiting counter as well as promotions and programs on the website and distribution of Dompet Dhuafa Waspada rolling out various programs poverty alleviation in North Sumatra & Aceh since 2015. The program operates in four fields, namely education, economics, health and social development. Dompet Dhuafa has distributed zakat in a productive way, such as by giving zakat in the form of capital loans in the form of community independent businesses in the form of virtue loans. Supporting increased utilization of productive zakat with the development of productive zakat in the form of business capital in order to develop UMK in Medan.